Pleomorphic Leiomyosarcoma of the Adrenal Gland in a Young Woman: A Case Report and Review of the Literature - Wang Y (OncoTargets and Therapy, 2020)
Yuanyuan Wang,1,* Yongliang Teng,2,* Shibo Na,3 Ye Yuan1 1Department of Anesthesiology, The First Hospital of Jilin University, Changchun, Jilin, People’s Republic of China; 2Department of Pathology, The First Hospital of Jilin University, Changchun, Jilin, People’s Republic of China; 3Department of Spinal Surgery, The First Hospital of Jilin University, Changchun, Jilin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ye Yuan Tel +86-13604430557Email yeyuan1225@sina.comAbstract: Leiomyosarcoma usually arises in the uterus, abdominal and urologic viscera, and walls of large and small blood vessels. However, primary adrenal leiomyosarcoma is extremely rare with only 39 cases previously reported in English-language literature. We report a case of a 29-year-old previously healthy woman with an incidentally found right adrenal-occupying lesion. CT scan revealed a right adrenal mass measuring 3.3× 3.4 cm in size. The tumor was successfully removed by laparoscopic adrenalectomy. Postoperative histopathologic examination showed spindle cells arranged in interlacing fascicles with pleomorphism and a high mitotic rate. An immunohistochemical examination showed positive staining for SMA, desmin, vimentin and H-caldesmon, and the diagnosis of a well-differentiated adrenal leiomyosarcoma was established. The patient received no other oncological treatment after surgery and currently has no evidence of residual disease or tumor recurrence according to imaging follow-up.Keywords: adrenal gland, adrenal gland neoplasms, leiomyosarcoma, adrenalectomy